South African Adolescents' Neighborhood Perceptions Predict Longitudinal Change in Youth and Family Functioning. (October 2018) - Tarantino, Nicholas; Goodrum, Nada M.; Salama, Christina; LeCroix, Rebecca H.; Gaska, Karie; Cook, Sarah L.; Skinner, Donald; Armistead, Lisa P.
This study examined South African early adolescent youth (aged 10-14 years) and their female caregivers ( N = 99 dyads) participating in an HIV prevention intervention over a period of 8 months. We examined youth perceptions of neighborhood cohesion, safety, and collective monitoring as they related to concurrent and longitudinal associations with youth (externalizing behavior and hope about the future) and family (parent-youth relationship quality, parental involvement, and parental responsiveness to sex communication) functioning while controlling for baseline characteristics. Neighborhood perceptions were significantly associated ( p < .05) with short- and longer term outcomes. Gender differences suggested a greater protective association of perceived neighborhood conditions with changes in functioning for boys versus girls. Unexpected associations were also observed, including short-term associations suggesting a link between better neighborhood quality and poorer family functioning. We account for the culture of this South African community when contextualizing our findings and conclude with recommendations for interventions targeting neighborhood contexts.